2022
DOI: 10.1101/2022.03.04.22271927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistence of targetable lesions, predicted therapy sensitivity and proteomes through disease evolution in pediatric acute lymphoblastic leukemia

Abstract: Childhood acute lymphoblastic leukemia (ALL) genome landscapes indicate that relapses often arise from subclonal outgrowths. However, the impact of clonal evolution on the actionable proteome and response to targeted therapy is not known. Here, we present a comprehensive retrospective analysis of paired ALL diagnosis and relapsed specimen. Targeted next generation sequencing and proteome analysis indicated persistence of genome variants and stable proteomes through disease progression. Although variant-targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Gene ontology enrichment analysis was performed using g:Profiler with an FDR of 5%. A list of pediatric cancer-associated proteins was derived from the sequencing panel used for the genome and transcriptome analyses of pediatric leukemias and solid tumors as detailed in Lorentzian et al (preprint) . The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE partner repository with the data set identifier PXD036910.…”
Section: Methodsmentioning
confidence: 99%
“…Gene ontology enrichment analysis was performed using g:Profiler with an FDR of 5%. A list of pediatric cancer-associated proteins was derived from the sequencing panel used for the genome and transcriptome analyses of pediatric leukemias and solid tumors as detailed in Lorentzian et al (preprint) . The mass spectrometry proteomics data have been deposited to the ProteomeXchange Consortium via the PRIDE partner repository with the data set identifier PXD036910.…”
Section: Methodsmentioning
confidence: 99%
“…1F). Among these, we quantified 154 of a set of 349 cancer-associated proteins that we had previously assembled with a focus on drivers and therapeutic targets in pediatric malignancies (28), confirming comprehensive coverage of the most relevant drivers and pathways (Fig. 1F).…”
Section: Proteomics Reveals Potentially Actionable Targets Of Settlementioning
confidence: 53%
“…This study sets up the basis to implement proteomics into molecular tumor profiling of patients under PROFYLE and other pediatric precision medicine initiatives. Previous retrospective cohort studies have demonstrated that proteome analysis can identify drug targets and contribute to rational treatment choices in pediatric cancers (28,44). Pediatric precision medicine initiatives such as ZERO and INFORM have showcased the application of functional precision oncology during diagnosis for various cancer types, thereby potentially offering more suitable treatment options.…”
Section: Discussionmentioning
confidence: 99%